ULTIMATE STRENGTH OF FLANGED-PERFORATED PLATES UNDER EDGE SHEAR LOADING (MT) - WANG WenSheng; SHANG Xin (Jixie qiangdu)
Cutouts are widely used in ships and offshore structures, which are used mainly for inspection, and they may be fitted for other purposes, such as passing pipes and reducing weight. In general, the existence of cutouts can reduce the structural strength, so the plates with cutouts（perforated plates） are given high importance at the structural design stage. In this regard, locally reinforced perforated plates are often used in shipyards to satisfy the structural buckling and ultimate strength requirements, but quantitative evaluations of the reinforced perforated plates have a little insufficient. To mitigate the reduction of the structural strength, flanged cutout has been adopted as a reinforcing method to achieve the structural buckling and ultimate strength increase, but no standard methodologies or recommendations are available for the cutout parameters of this stiffener. In this paper, a series of numerical studies were undertaken to analyze the buckling and ultimate strengths of different thickness flanged-perforated plates, for various cutout parameters（cutout radius, flanging length and flanging angle） under edge shear loading condition. The results can provide references for the design of flanged-cutouts in engineering.